Criteria for selecting nominated subcontractors in commersial building construction / Muhandiramge Nimashi Navodana Rodrigo and Balasooriya Arachige Kanchana Shiromi Perera - Muhandiramge, Nimashi Navodana Rodrigo; Balasooriya Arachige, Kanchana Shiromi Perera (Faculty of Architecture, Planning and Surveying, 2017)
Construction industry employs Nominated Subcontractors (NSCs) who may not possess the required expertise. Hence various issues tend to arise affecting the success of the project. On the other hand selection of subcontractor plays a pivotal role to project’s success. Therefore, the issues caused by these NSCs and the actions required to prevent them were identified from the literature, validated through interviews and ranked through a questionnaire survey. ‘Delays caused by subcontractor’ is ranked as the most critical issue which arises due to improper selection of NSCs. The most important action that will prevent this issue is to make the NSC’s program of Works to fall in line with Main Contractor’s program of Works. Subsequently the next most critical issue aroused due to the improper selection was recognized as subcontractor’s incompetency and the most suitable action to prevent this issue is to check subcontractor’s experience, proficiency and capacity to deliver quality work on time. Finally, selection criteria were proposed to prevent the issues arising from selection of NSCs. The most significant criteria to avoid the issue, ‘delays caused by subcontractor’ was recognized as ‘progress’. Afterwards the overall suitability of the criteria financial capacity; experience; resources; work quality; progress; design quality; site safety; general obligations were investigated. The calculated overall suitability scores of the criteria and the overall suitability bands revealed that the criteria were considered as ‘suitable’ to prevent the issue ‘subcontractor insolvency’ and for the other issues, the criteria were identified to be ‘somewhat suitable’.